SOME FIXED POINT THEOREMS ON GENERALIZED INTUITIONISTIC FUZZY METRIC SPACES - JEYARAMAN, M.; SOWNDRARAJAN*, S. (International Journal of Mathematical Archive, 2018)
In this paper, we introduce the concepts of convergent sequence, Cauchy sequenceÂ  inÂ  generalized intuitionistic fuzzy metric space and some common fixed point theorems for some generalized contraction mappings are established.